Badiiy hikoyalardan foydalanish orqali ingliz tilini oʻrganuvchilarning kommunikativ kompetensiyasini rivojlantirishning samarali yoʻllari - Bisenova, A (SCIENCE and SOCIETY, 2025)
The article describes the effectiveness of using literary stories in the development of communicative competence of English language learners. The research results showed that literary stories serve to expand students' vocabulary, increase the naturalness of speech, cultural understanding, and trust in communication. Also, through
Keywords: literary storytelling; communicative competence; teaching English; interactive method; cultural context; creative thinking; empathy; motivation; communicative approach